Dyadic Aspects of Sexual Well-Being in Men with Laser-Treated Penile Carcinoma - Elisabet Skeppner, PhD; Kerstin Fugl-Meyer, PhD (Sexual Medicine, 2015)
Introduction: Coping with cancer, its treatment and recovery are dyadic processes within a relationship. Sexual dysfunctions and problems of penile cancer may add to the demands of coping. Aim: The prospective study aimed to describe the dyadic aspects of sexual well-being and life satisfaction before and 1 year after organ-sparing laser treatment of penile carcinoma. Methods: A consecutive series of 29 patients with penile carcinoma suitable for laser treatment were included together with their partners, median age 60 (37–73) years and 57 (30–72) years, respectively. Median length of relationship was 29 years (1–54 years). The participants completed structured interviews before treatment, at 6 months' and 12 months' follow-up. The interview addressed sexual activities, sexual functions, verbal (sexual) communication, and life satisfaction. Main Outcome Measures: Three well-validated instruments were included: Hospital Anxiety and Depression Scale, International Index of Erectile Function-5, and Life Satisfaction checklist, LiSat-11. The interviews contained the same questions for patients and partners at all three measuring points. Results: There was a high level of within-couple agreement on sexual activities, sexual function, and life satisfaction before and after organ-sparring treatment. No significant differences between interview data at 6 and 12 months' follow-up occurred. Before treatment, sexual dysfunctions were common among men, especially decreased sexual interest and dyspareunia. At follow-up, increased sexual function was found, with the exception of erectile function and women's orgasm. A rather high proportion was being unsatisfactory sexually inactive. Few had an ongoing verbal (sexual) mutual communication. Couples with an active sexual life at follow-up showed coherence in high satisfaction with life as a whole. Conclusion: A high level of within-couple agreement concerning sexuality and life satisfaction points to the necessity of including an adequate sexological case history, counseling, and treatment for this group of patients and their partners. Skeppner E and Fugl-Meyer K. Dyadic aspects of sexual well-being in men with laser-treated penile carcinoma. Sex Med 2015;3:67–75.